Skrining Risiko Metabolik dan Edukasi Pola Hidup Healthy Longevity untuk Pencegahan Komplikasi pada Penderita Diabetes Mellitus dan Hipertensi di Wilayah Kerja Puskesmas Cempae Kota Pare-pare - Aida ayu Chandrawati; Syahrianti Sarea; Novi Safitri Nurdin (LOSARI DIGITAL, 2026)
Noncommunicable diseases such as diabetes mellitus and hypertension are chronic conditions with a high risk of complications. Although they receive treatment, many patients still have uncontrolled risk factors, necessitating a promotive and preventive approach. This community service activity aims to improve public knowledge and awareness through metabolic risk screening and education on a healthy longevity lifestyle. The activity methods included screening using a simple card based on clinical and lifestyle parameters, as well as education on healthy eating, physical activity, medication adherence, and routine check-ups. Evaluation was conducted using pre-tests and post-tests on 143 participants with Diabetes Mellitus and Hypertension. Screening results showed that 83.9% of participants were in the high metabolic risk category and 16.1% in the moderate category. After the education session, the average percentage of correct answers increased from 42.5% to 91.8%. The results of the paired t-test showed a highly significant difference between the pre-test and post-test scores (p < 0.001). This activity demonstrates that metabolic risk screening and education on a healthy longevity lifestyle are effective in improving public knowledge and awareness and support the prevention of chronic disease complications.